2019
DOI: 10.1021/jacs.8b12381
|View full text |Cite
|
Sign up to set email alerts
|

Structural Sensitivities in Bimetallic Catalysts for Electrochemical CO2 Reduction Revealed by Ag–Cu Nanodimers

Abstract: Understanding the structural and compositional sensitivities of the electrochemical CO2 reduction reaction (CO2RR) is fundamentally important for developing highly efficient and selective electrocatalysts. Here, we use Ag/Cu nanocrystals to uncover the key role played by the Ag/Cu interface in promoting CO2RR. Nanodimers including the two constituent metals as segregated domains sharing a tunable interface are obtained by developing a seeded growth synthesis, wherein preformed Ag nanoparticles are used as nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
379
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 453 publications
(397 citation statements)
references
References 65 publications
14
379
1
3
Order By: Relevance
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 98%
See 2 more Smart Citations
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 98%
“…Interestingly, although CO is the predominant reaction product for Ag–Cu in the selective ECR, which is derived mainly from synergistic reactions rather than pure dilution effects between Ag and Cu, it should be noted that Cu and Cu‐based catalysts including Ag–Cu also have the potential to convert CO 2 to various hydrocarbons such as C 2 H 6 , CH 4 , or/and oxygenates such as C 2 H 5 OH, CH 3 OH, HCHO . Further studies demonstrated that the selectivity and activity of these bimetallic Ag–Cu electrocatalysts for the ECR to CO were closely related to the atomic distributions and ratios of Ag and Cu …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inevitably,i ti sa lso influenced by the pH of the electrolyte. [35] The FE for CO productiono ver SMFeSCN reached approximately9 9% at À0.55 V, whereas that over SMFe reached only 87 %a tt he same potential. To furtherc onfirmt he CO 2 RR performance, the liquid phase after 3hreactionw as investigated by 1 HNMR spectroscopy,b ut no products were detected,a ss hown in Figure S2 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 93%
“…The FE of gaseous productsw as calculated by GC analysis. [35] The FE for CO productiono ver SMFeSCN reached approximately9 9% at À0.55 V, whereas that over SMFe reached only 87 %a tt he same potential. Furthermore, over aw ide range of potentials from À0.45 to À0.85 V, ah igh FE for CO productiono verS MFeSCN (!…”
Section: Resultsmentioning
confidence: 93%